2017
DOI: 10.1186/s13098-017-0300-7
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes does not impair the physical capacity of non-sedentary adolescents

Abstract: BackgroundType 1 diabetes patients have a higher risk of developing hypoglycemia or hyperglycemia during physical activity, which may compromise their safety during exercise but results regarding the exercise capacity of patients with type 1 DM when compared to control subjects have been contradictory.AimTo evaluate if type 1 diabetes affects the capacity of adolescents to exercise.MethodsThe study enrolled 37 adolescents in stage 2–4 of the Tanner scale, aged from 10 to 14 years, 21 with type 1 diabetes and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…Our observation is in line with the aforementioned studies [22,23]. In our study group we did not find any relationship between HbA1c concentration and Cooper test results, which is consistent with the findings of Nascimiento et al [22]. On the other hand, Nguyen et al demonstrated that children with poor glycemic control (HbA1c > 74.9 mmol/mol for > 9months) displayed lower maximum VO2 peak than healthy controls [23], while those with HbA1c < 58 mmol/mol were not different from healthy peers.…”
Section: Physical Fitness Of Children With T1dmsupporting
confidence: 94%
See 3 more Smart Citations
“…Our observation is in line with the aforementioned studies [22,23]. In our study group we did not find any relationship between HbA1c concentration and Cooper test results, which is consistent with the findings of Nascimiento et al [22]. On the other hand, Nguyen et al demonstrated that children with poor glycemic control (HbA1c > 74.9 mmol/mol for > 9months) displayed lower maximum VO2 peak than healthy controls [23], while those with HbA1c < 58 mmol/mol were not different from healthy peers.…”
Section: Physical Fitness Of Children With T1dmsupporting
confidence: 94%
“…We demonstrated that children with T1DM who participated in the present study, all with good or suboptimal glycemic control, displayed fitness level similar to that of the general population of their peers. Our observation is in line with the aforementioned studies [22,23]. In our study group we did not find any relationship between HbA1c concentration and Cooper test results, which is consistent with the findings of Nascimiento et al [22].…”
Section: Physical Fitness Of Children With T1dmsupporting
confidence: 94%
See 2 more Smart Citations
“…Furthermore, significant relationships between physiological parameters of exercise performance and anthropometric variables for healthy controls are shown in Table 3. (24).…”
Section: Association Between Diabetes Characteristics and Functional mentioning
confidence: 99%